Credit unions and competition in the brazilian financial intermediation system - Santos, Marcelo Henrique Shinkoda (2021)
Unlike traditional banks, the reform of credit unions in the national financial intermediation system did not have a specific program named and publicized nationally, as was the Program to Stimulate the Restructuring and Strengthening of the National Financial System (PROER – as is their acronym in Portuguese). However, the reform of credit unions has been based on the north, whereas financial management improved, the Central Bank of Brazil followed with an increasingly flexible regulatory framework. In this sense, since 2000, credit unions gained the "right" to open their banks and expand the municipalities in which they operate, concerning population size. "Resolved" the problem of moral hazard with the creation of a guarantee fund, and in an aggreged form, they reached asset and liability levels close to those of traditional banks. Given this context, this thesis aimed to evaluate the competitive dynamics of credit unions in Brazilian financial intermediation. Specifically, it sought to assess the dynamics of credit unions in the financial inclusion process, comparing them with the dynamics of traditional banks. Furthermore, this thesis also sought to identify the degree of maturity of credit unions from the merger processes between 2008 and 2020. Finally, this thesis sought to verify whether individual credit unions compete with bank branches for inputs in the places where they coexist. In summary, the results indicate that only credit unions (in a set that includes private banks, public banks, credit unions, and FinTechs) are positively associated with financial inclusion in adverse times. Moreover, this relationship is associated with the credit unions' maturity level that competes with bank agencies for input, even in practical entry barriers. Thus, it can be concluded that credit unions' maturity increased between 2008 and 2020 and that they have stood out in the financial intermediation market without losing the cooperative spirit. Keywords: Credit Unions. Banks. Financial Intermediation. Competition.